Compendium of food additive specifications : (FAO/WHO, 2006)
This document contains food additive specifications monographs, analytical methods and other information, prepared at the sixty-seventh meeting of the Joint FAO/WHO Committee on Food Additives (JECFA), which was held in Rome, Italy, from June 20 to 29, 2006. The specifications monographs provide information on the identity and purity of food additives used directly in foods or in food production. The main three objectives of these specifications are to identify the food additive that has been subjected to testing for safety, to ensure that the additive is of the quality required for use in food or in processing, and to reflect and encourage good manufacturing practice. This publication and other documents produced by JECFA contain information that is useful to all those who work with or are interested in food additives and their safe use in food.